2005
DOI: 10.1007/s00221-005-0100-4
|View full text |Cite
|
Sign up to set email alerts
|

The effect of gaze direction on sound localization in brain-injured and normal adults

Abstract: This study examined the effects of eye position on sound localization in normal and brain lesion subjects. On the assumption that cerebral lesions may disrupt the representation of or attention to auditory space in the contralesional hemispace, we predicted that subjects with brain lesions would be less accurate in localizing sounds in the contralesional hemispace. In Experiment 1 we showed that gazing to the midline subjects with brain lesions were indeed impaired in localizing sounds in the contralesional he… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
5
0

Year Published

2008
2008
2016
2016

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 64 publications
3
5
0
Order By: Relevance
“…Second, the gradient was demonstrated while the directions of gaze and attention were dissociated. This confirms that the intelligibility gradient found in Experiment 1A was not simply due to a preference to allocate attentional resources in the direction of gaze (Lie & Branch Coslett, 2006).…”
Section: Resultssupporting
confidence: 82%
See 1 more Smart Citation
“…Second, the gradient was demonstrated while the directions of gaze and attention were dissociated. This confirms that the intelligibility gradient found in Experiment 1A was not simply due to a preference to allocate attentional resources in the direction of gaze (Lie & Branch Coslett, 2006).…”
Section: Resultssupporting
confidence: 82%
“…Numerous studies have shown that stimuli at lateralized positions are not as well processed as are those at positions nearer to the midline (e.g., Carlile, Leong, & Hyams, 1997;Mills, 1958). Furthermore, Lie and Branch Coslett (2006) and Rorden and Driver (1999) demonstrated that gaze direction provides a processing advantage, possibly due to an increase in the allocation of attention to the region corresponding to gaze direction. Thus, the apparent gradient of attention could also have been due to observers' gazes being directed forward toward the attended central loudspeaker.…”
Section: Resultsmentioning
confidence: 99%
“…Similarly, a group of neurons in the frontal eye field becomes active before a saccade is executed either toward an auditory or a visual target (Russo and Bruce, 1994). In addition, behavioural studies have demonstrated improved performance for sounds at fixation (Gopher, 1973; Hublet et al, ​1976, ​1977; Jones and Kabanoff, 1975; Morais et al, 1980; Reisberg et al, 1981), as well as for sounds presented at the destination of an upcoming saccade (Rorden and Driver, 1999; Lie and Coslett, 2006), suggesting that eye gaze may affect auditory processing in a spatially specific fashion.…”
Section: Introductionmentioning
confidence: 99%
“…'s deficit demonstrated in Experiment 4 is consistent with our hypothesis that he is unable to bind information computed in the ventral and dorsal visual systems. In previous work we have demonstrated that performance on tasks that appear to have no explicit spatial dimension-for example, languagemay be influenced by spatial factors (Coslett, 1999;Coslett, Schwartz, Goldberg, Haas, & Perkins, 1993; see also Lie, McCrae, & Coslett, 2006). On the basis of these data, we argued that stimuli with no apparent spatial dimension are marked for location; furthermore, we argued that a disruption of the binding of this location information to language and other sensorimotor systems may underlie these spatial effects (Coslett, 1999).…”
Section: Discussionmentioning
confidence: 97%